Fulfillment of civil rights of extramarital children and its effect on social dimensions - Alfian Qodri Azizi; Ali Imron; Bagas Heradhyaksa (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2020)
This article examines the fulfillment of the civil rights of extramarital children which has become a controversy since the issuance of the Constitutional Court decision no. 46/PUU-VIII/2010, which is considered as a progressive and responsive measure to guarantee children's rights. However, the content of this decision is considered to violate Islamic norms in giving family lineage to extramarital children for it will create a stigma that one does not need a sacred marriage institution if he only wants to establish a civil or lineage relationship with his biological father; instead, it only requires evidence based on science and technology or others in court. This article answers the questions of how to interpret the concept of the civil rights of extramarital children to avoid conflicts with Islamic norms and what are the philosophical and sociological benefits of fulfilling civil rights for extramarital children. This study is qualitative in nature. It is focused more on conceptual ideas based on library research using conceptual and case approaches. It was found that (1) the civil rights of extramarital children are not a lineage right but compensation from their biological father as a form of moral responsibility; (2) philosophically, the civil rights of extramarital children are to fulfill the value of social justice which is distributive and, sociologically, these rights create a prosperous social condition for society by fulfilling the civil rights of the next generation of the nation covering their physical, mental, spiritual, and intellectual needs.